Analysis and analytical methods in the planning system of health care institutions - Sysiuk, Svitlana; Yunger, Vitaliy; Kyryk, Vasyl; Timchev, Marko (Public Policy and Accounting, 2023)
In the article, a critical assessment of the planning system in the field of health care in modern conditions was carried out, a list of plans and their relationship with the management of the activities of a medical institution were identified. It is proposed to strengthen the adaptability of plans to the requirements of the management system; the principles of improvement of the plans were formed (in terms of their standardization and content content). On the basis of the method of generalization and critical analysis, the main problem areas in planning have been identified, for which the application of analysis and its methods will be a reasonable solution. Attention is focused on areas of improvement and the planning algorithm in accordance with the developed author's approach. The development of such an approach is based on an assessment and analysis for the purpose of identifying problems in planning. Thanks to these methods, a study of the indicators of financial provision of health care was also carried out, directions for solving management tasks were formed in terms of improving planning and analytical work. Synthesis, grouping, generalization, comparison was used to identify directions and improve the planning methodology algorithm, including by applying analytical methods in its implementation. Due to this, using tabular and graphic methods, formalization, an approach to conducting a comprehensive assessment of the current state of activity and resources of the health care entity was formed, and its main stages were described and the necessary comparative indicators were determined. Implementation of the proposed approach makes it possible to improve planning in health care and contributes to the development of real and objective plans for the activities of medical institutions.